2020
DOI: 10.2298/pac2004314k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of CeLaMO2 (M: Sm, Gd, Dy) compounds for solid ceramic electrolytes

Abstract: In this study, pure CeO2 and Ce0.85La0.10M0.05O2 (M: Sm3+, Gd3+, Dy3+) solid electrolytes were synthesized using the sol-gel method and sintered at 1350?C for 12 h. X-ray diffraction (XRD) was used for crystal structure characterization of the ceramic solid electrolytes. After sintering, all prepared solid electrolytes were indexed to be cubic crystal lattices. The thermal properties of the prepared samples were investigated by thermogravimetric (TG) and differential thermal analysis (DTA) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…With the further comparison of the values for conductivity obtained for similar materials based on oxygen ion conductors (multi-doped ceria materials) investigated in previous literature reports [12,19,20,24,25,[30][31][32][33][34]37], it may be observed that present results for the SPRT samples are in the similar range while for the MGNP samples are noticeably higher. What is more, referring to some existing studies [32,38], the present results are higher for a whole order of magnitude even for the SPRT samples.…”
Section: Electrical Conductivitysupporting
confidence: 64%
“…With the further comparison of the values for conductivity obtained for similar materials based on oxygen ion conductors (multi-doped ceria materials) investigated in previous literature reports [12,19,20,24,25,[30][31][32][33][34]37], it may be observed that present results for the SPRT samples are in the similar range while for the MGNP samples are noticeably higher. What is more, referring to some existing studies [32,38], the present results are higher for a whole order of magnitude even for the SPRT samples.…”
Section: Electrical Conductivitysupporting
confidence: 64%
“…108 To improve its performance, Sm 3+ , Gd 3+ , and Dy 3+ are doped. 109 Sm 3+ and Gd 3+ doped CeO 2 electrolyte (SDC, GDC) show significantly improved conductivity. GDC and SDC are often combined with YSZ to make use of their advantages.…”
Section: In O-soecmentioning
confidence: 99%